Community-Based Mangrove Conservation Strategies in the Lembar Selatan Ecotourism Area, West Lombok - Isrowati, Isrowati; Jupri, Ahmad; Rohyani, Immy Suci; Ahyadi, Hilman (Jurnal Biologi Tropis, 2026)
Mangrove degradation in Lembar Selatan, West Lombok, threatens ecological functions and community-based ecotourism. This study evaluated site physicochemical conditions, mangrove vegetation structure, community conservation practices, and management strategies. Physicochemical measurements were obtained from 18 water samples collected across the vegetation plots. Mangrove vegetation was assessed in purposively located nested plots (10 × 10 m for trees, 5 × 5 m for saplings, and 2 × 2 m for seedlings). Community participation was explored through in-depth interviews with 10 informants, comprising purposively selected residents and ecotourism managers; qualitative data were analyzed using the Miles–Huberman framework and triangulation. Air and water temperatures ranged from 27.3 to 29.0 °C, pH from 6.9 to 7.39, and salinity from 11.2 to 23.2 ppt, with muddy-sand substrate. Rhizophora mucronata. dominated all growth stages, with IVI values of 200.00% for seedlings, 267.70% for saplings, and 246.03% for trees; Avicennia alba and Sonneratia alba occurred only at sapling and tree stages. Community actions include nursery management, planting, education, and mangrove utilization. SWOT synthesis generated alternatives focused on participatory rehabilitation, institutional coordination, community-based attractions, and ecological differentiation. The findings support diversified, site-matched rehabilitation and transparent stakeholder validation of management priorities.